2006
DOI: 10.2174/092986606776819538
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminus Leader Sequence of Shiga Toxin (Stx) 1 Is Essential for Production of Active Recombinant Protein in E. coli

Abstract: Escherichia coli clones expressing recombinant shiga toxin (Stx1) and its derivatives Stx1-A and Stx1-B subunits were established to release the proteins into periplasmic space. The expression was examined by SDS-PAGE to visualize the subunits. The secreted assembled subunits were extracted with polymyxin B and assessed for biological activity. The results showed that the presence of N-terminus leader sequence of the gene is essential for assembly of the subunits to yield biologically active holotoxin (AB5). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Stx2 seems to have comparable catalytic activity to Stx1 [19]. The A and B subunits of Stx1 and Stx2 possess N-terminal signal sequences which facilitate their transport to the periplasm, where they assemble into mature toxin [20,21]. Expression of Stx is driven by a late-phase phage promoter, which is strongly activated upon induction of the bacterial SOS response.…”
Section: Introductionmentioning
confidence: 99%
“…Stx2 seems to have comparable catalytic activity to Stx1 [19]. The A and B subunits of Stx1 and Stx2 possess N-terminal signal sequences which facilitate their transport to the periplasm, where they assemble into mature toxin [20,21]. Expression of Stx is driven by a late-phase phage promoter, which is strongly activated upon induction of the bacterial SOS response.…”
Section: Introductionmentioning
confidence: 99%
“…Only one pair of primers (P1 and P2) was used to amplify the whole stx1 gene and indirectly used E. coli O157:H7 as a template to amplify the entire stx1 gene. This is done rather than amplifying the genes of the subunits or initially purifying from a toxin‐converting phage, then using the toxin‐converting phage as a PCR template, which is much easier than the method of previous investigators . Furthermore, we could get final yield of the purified rStx1 ranged from 2 to 3 mg/L by one‐step nickel affinity gel column chromatography, which could be comparable yield from some previous affinity purification methods of Stx1 using globotriaosylceramide (Gb3) or egg white glycoprotein‐immobilized resins [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…showed that the presence of the N‐terminal leader sequence of the gene is essential for assembly of the subunits to yield biologically activity holotoxin (AB 5 ). The absence of the leader sequence did not affect the expression of the subunits, but it did disrupt the holotoxin assembly . However, in these studies, the construction of recombinant plasmid is more complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Shiga toxins as holotoxins were obtained from already cloned genes in pBAD expression vector with L-arabinose; the best concentration of L-arabinose was 2% ( 13 ). The toxins were sterilized by filtering through a sterile filter (Schleicher and Schuell, Germany) and the protein concentration of Stxs was estimated by the Bradford method.…”
Section: Methodsmentioning
confidence: 99%